2017
DOI: 10.18632/oncotarget.20236
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of carbonic anhydrase IX induces cell motility by activating matrix metalloproteinase-9 in human oral squamous cell carcinoma cells

Abstract: Oral cancer is a solid malignant tumor that is prone to occur following hypoxia. There are no clear studies showing a link between hypoxia and oral carcinogenesis. Carbonic anhydrase IX (CAIX), which is a hypoxia-induced transmembrane protein, is highly expressed in various types of human cancer. However, the effects of CAIX on the metastasis of human oral cancer cells and the underlying molecular mechanisms have not been clarified. In this study, we observed that CAIX overexpression increased the migratory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…The Src and MAPK pathways have been reported to be involved in the upstream signaling pathways of MMP‐2 expression and cancer metastasis . Therefore, the effects of geraniin on the expression of Src and MAPK pathways were investigated to elucidate their underlying mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Src and MAPK pathways have been reported to be involved in the upstream signaling pathways of MMP‐2 expression and cancer metastasis . Therefore, the effects of geraniin on the expression of Src and MAPK pathways were investigated to elucidate their underlying mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The Src and MAPK pathways have been reported to be involved in the upstream signaling pathways of MMP-2 expression and cancer metastasis. 16,32,33 Therefore, the effects of geraniin on the expression of Src and MAPK pathways were investigated to elucidate their underlying mechanisms. The results of the Western blot assay revealed that the phosphorylation of Src, focal adhesion kinase (FAK), and ERK1/2 decreased in SCC-9 cells but not the phosphorylation of the JNK1/2 and p38 pathways ( Figure 5).…”
Section: Effects Of Geraniin On Mapk and Src Pathwaysmentioning
confidence: 99%
“…MMP‐2 is highly observed in metastatic cases of OSCC, and its expression and activity against ECM during metastasis have been linked to the promotion of cell metastasis . Earlier reports have indicated that the mitogen‐activated protein kinase kinase (MEK)/mitogen‐activated protein kinase (MAPK) family and the focal adhesion kinase (FAK)‐Src pathway are critical points in the regulation of cell migration, invasion, adhesion, proliferation, and MMP expression …”
Section: Introductionmentioning
confidence: 99%
“…MMPs regulate ECM to facilitate cell migration by removing barriers. Specifically, the expressions of MMP‐2 and MMP‐9 are associated with the invasive potential of cancer . Previous studies also reported that epigallocatechin gallate prevents transforming growth factor beta 1‐induced MMP‐2 in ARPE‐19 cells .…”
Section: Introductionmentioning
confidence: 94%
“…Specifically, the expressions of MMP-2 and MMP-9 are associated with the invasive potential of cancer. 9,11,12 Previous studies also reported that epigallocatechin gallate prevents transforming growth factor beta 1-induced MMP-2 in ARPE-19 cells. 13 Moreover, studies have reported that MMP-2 expression correlates significantly with the PVR grade.…”
Section: Introductionmentioning
confidence: 97%